1988
DOI: 10.1016/s0022-5347(17)42066-0
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Testicular Injury from External Trauma

Abstract: Among 79 patients with testicular injury as a result of external trauma 5 had bilateral injury. Such injury occurred in only 1 of 66 patients (1.5 per cent) with blunt trauma versus 4 of 13 (31 per cent) with penetrating trauma. Bilateral ruptures were managed by bilateral partial orchiectomy in 2 cases, and orchiectomy with contralateral débridement and suturing in 1. Of 2 patients with unilateral rupture and contralateral contusion the contusions were treated by evacuation of the hematoma and the ruptures we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 3 publications
1
22
0
Order By: Relevance
“…Defense mechanisms of the testicle itself in clude: the mobility within the scrotum, the tough and resilient tunica albuginea, and the withdrawal from dan ger by cremaster contraction [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Defense mechanisms of the testicle itself in clude: the mobility within the scrotum, the tough and resilient tunica albuginea, and the withdrawal from dan ger by cremaster contraction [15,18].…”
Section: Discussionmentioning
confidence: 99%
“…Two single-institution series reported between 31 and 67 cases of testicular trauma requiring surgery in a 10-year period [16,85]. Quesada et al [85] showed that men with unilateral testicular trauma requiring orchiectomy or open repair failed to show a significant decrease in the follow-up sperm density.…”
Section: Testicular Traumamentioning
confidence: 99%
“…Quesada et al [85] showed that men with unilateral testicular trauma requiring orchiectomy or open repair failed to show a significant decrease in the follow-up sperm density. Cass et al [16] reviewed the literature on bilateral testicular trauma and revealed that only four patients have had followup semen analysis, and these showed an average sperm density of 37x106)'cc, with none having fewer than 20x 106 sperm/cc. Spermatogenic dysfunction in testicular trauma patients appears to be secondary to direct cell injury and, perhaps due, to the formation of antisperm antibodies from disruption of the blood-testes barrier.…”
Section: Testicular Traumamentioning
confidence: 99%
“…Bilateral injuries occur more commonly in the setting of penetrating trauma than in the other forms of trauma. 44 Penetrating injuries can disrupt the tunica albuginea, as well as penetrate the testicular parenchyma itself, causing a fracturelike injury. Ultrasound is capable of assessing the degree of injury to direct appropriate management.…”
Section: Penetrating Traumamentioning
confidence: 99%